2017
DOI: 10.1136/annrheumdis-2016-210960
|View full text |Cite
|
Sign up to set email alerts
|

European evidence-based recommendations for diagnosis and treatment of childhood-onset systemic lupus erythematosus: the SHARE initiative

Abstract: Childhood-onset systemic lupus erythematosus (cSLE) is a rare, multisystem and potentially life-threatening autoimmune disorder with significant associated morbidity. Evidence-based guidelines are sparse and management is often based on clinical expertise. SHARE (Single Hub and Access point for paediatric Rheumatology in Europe) was launched to optimise and disseminate management regimens for children and young adults with rheumatic diseases like cSLE. Here, we provide evidence-based recommendations for diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
167
0
26

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(196 citation statements)
references
References 105 publications
3
167
0
26
Order By: Relevance
“…Lack of adherence to therapy can be as high as 50%, and has been associated with higher persistent disease activity and poorer renal outcomes 78–81. Measuring medication (trough) levels to unmask non-compliance is advisable 15. RCTs in adult LN have shown that time is needed to reach complete renal response for at least 3–6 months 51.…”
Section: Recommendations For Ln—treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of adherence to therapy can be as high as 50%, and has been associated with higher persistent disease activity and poorer renal outcomes 78–81. Measuring medication (trough) levels to unmask non-compliance is advisable 15. RCTs in adult LN have shown that time is needed to reach complete renal response for at least 3–6 months 51.…”
Section: Recommendations For Ln—treatmentmentioning
confidence: 99%
“…SHARE recommendations for diagnosis and treatment of cSLE (excluding LN) have also been published 15. Here, the SHARE recommendations for LN are presented.…”
Section: Introductionmentioning
confidence: 99%
“…Despite distinct differences in the phenotype and pathogenesis of JSLE 7 , international recommendations for the treatment of JSLE 8 The aim of this present study was to use observational data from the UK JSLE Cohort Study 1 , to compare effectiveness of MMF vs. IVCYC induction treatments in patients with juvenile-onset LN, assessing response to treatment, damage accrual, time to achievement of inactive LN, and time to subsequent LN flare.…”
Section: Introductionmentioning
confidence: 99%
“…The European initiative SHARE (Single Hub and Access point for paediatric Rheumatology in Europe) aims to optimize care for children and young adults with Paediatric Rheumatic Diseases (6)(7)(8)(9)(10)(11). For rare forms of childhood systemic vasculitis (PAN, ANCA-associated vasculitides (AAV), and TA), the objective was to design cross-cutting and disease-specific evidence-based recommendations for diagnosis and treatment.…”
Section: Rare Forms Of Primary Systemic Vasculitis Include: Polyartermentioning
confidence: 99%